Improving service quality by capitalising on an integrated Lean Six Sigma methodology. (30th March 2006) - Su, Chao-Ton; Chiang, Tai-Lin; Chang, Che-Ming
Today, service processes are usually slow processes which are consequently prone to poor service quality. In addition, service has the inherent characteristic of heterogeneity, which means there is variation in service quality that is unsatisfactory to the customer. Fortunately, these issues can be addressed by combining the speed advantage of Lean discipline with Six Sigma's capability of uniform process output. This paper aims to develop and apply an integrated Lean Six Sigma methodology in a service-quality improvement endeavour. An empirical case study of IT (Information Technology) help-desk service was utilised to examine the effectiveness of the methodology.